Characterization of Ornithine TransCarbamylase (OTC) gene polymorphisms in the West Algerian population and association with myocardial infarction - Djabaria Naima Meroufel; Sounnia Médiène-Benchekor; Julie Dumont; Philippe Amouyel; Thierry Brousseau; Soraya Benhammamouch (Journal de la Faculté de Médecine d'Oran, 2017)
Objective - The polymorphism rs5963409 of the gene coding for Ornithine Trans- Carbamylase (OTC) has been shown to be associated with hypertension and coronary vasomotricity in Caucasian populations. On the basis of these results, we chose to study the association of two polymorphisms rs5963409, located at the 5 ‘region of the promoter and rs1800321, located at exon 2, of the OTC gene with the risk of The occurrence of myocardial infarction (MI) and the systolic and diastolic blood pressure values. Patients and methods- the SNPs were characterised in a case control study (70 cases vs 68 controls) based on the male population originating from Oran, Algeria ECTOR study. Genetic characterization of both polymorphisms was carried out using the Polymerase Chain Reaction (PCR) technique followed by enzymatic digestion. Results -The rs5963409 and rs1800321 polymorphisms are not associated with MI or changes in systolic and diastolic blood pressure values. However, we observed a significant interaction between the polymorphism rs5963409 and the Body Mass Index (BMI) on the risk of the occurrence of MI. Conclusion: Our results indicate that both polymorphisms of the OTC gene are not associated with MI in the West-Algerian population.